A new genus and species of the planthopper tribe Augilini Baker (Hemiptera, Caliscelidae, Ommatidiotinae) from Thailand and China - Che, Yanli; Zhang, Yalin; Webb, M. D. (Zootaxa, 2009)
In the present paper a new genus and new species of caliscelid planthopper (Hemiptera: Fulgoromorpha), Pseudosymplanella nigrifasciata are described and illustrated. The species is recorded from China and from bamboo in Thailand. This represents the first record of the tribe Augilini from Thailand and the first record of bamboo as a host for a member of this tribe. A key to genera of Augilini is provided and notes given on Augilina longipes Melichar.